Editorial. Relating systems thinking and design VII: Advancing Design Methodologies for Social and Environmental Systems - Davidová , Marie; Sweeting, Ben; Sevaldson, Birger (FormAkademisk, 2020)
This special issue of FormAkademisk comprises a selection of articles developed from presentations at the seventh Relating Systems Thinking and Design (RSD7) symposium, held at Politecnico di Torino, Turin, October 23-26, 2018 (Barbero, 2018). RSD7 saw the launch of the Systemic Design Association (SDA), a membership organisation for the expanding community that has developed through the RSD conferences. The present issue is the second collection of articles from RSD7 to be published in FormAkademisk following the one released earlier this year (Davidova et al., 2020). These issues are the latest contributions to the ongoing relationship between the journal and the RSD conference series (Forlizzi et al., 2017; Hensel et al., 2019; Jones, 2014; Sevaldson, 2018; Sevaldson & Ryan, 2014).